Time trends in the aetiology of prosthetic joint infections: a multicentre cohort study. (August 2016) - Benito, N.; Franco, M.; Ribera, A.; Soriano, A.; Rodriguez-Pardo, D.; Sorlí, L.; Fresco, G.; Fernández-Sampedro, M.; Dolores del Toro, M.; Guío, L.; Sánchez-Rivas, E.; Bahamonde, A.; et al.
Abstract: It is important to know the spectrum of the microbial aetiology of prosthetic joint infections (PJIs) to guide empiric treatment and establish antimicrobial prophylaxis in joint replacements. There are no available data based on large contemporary patient cohorts. We sought to characterize the causative pathogens of PJIs and to evaluate trends in the microbial aetiology. We hypothesized that the frequency of antimicrobial-resistant organisms in PJIs has increased in the recent years. We performed a cohort study in 19 hospitals in Spain, from 2003 to 2012. For each 2-year period (2003–2004 to 2011–2012), the incidence of microorganisms causing PJIs and multidrug-resistant bacteria was assessed. Temporal trends over the study period were evaluated. We included 2524 consecutive adult patients with a diagnosis of PJI. A microbiological diagnosis was obtained for 2288 cases (90.6%). Staphylococci were the most common cause of infection (1492, 65.2%). However, a statistically significant rising linear trend was observed for the proportion of infections caused by Gram-negative bacilli, mainly due to the increase in the last 2-year period (25% in 2003–2004, 33.3% in 2011–2012; p 0.024 for trend). No particular species contributed disproportionally to this overall increase. The percentage of multidrug-resistant bacteria PJIs increased from 9.3% in 2003–2004 to 15.8% in 2011–2012 (p 0.008), mainly because of the significant rise in multidrug-resistant Gram-negative bacilli (from 5.3% in 2003–2004 to 8.2% in 2011–2012; p 0.032). The observed trends have important implications for the management of PJIs and prophylaxis in joint replacements.